RISK FACTORS FOR SMELL AND TASTE DISORDER IN MILD AND MODERATE COVID-19 IN SEMARANG - Dewi, Anna Mailasari Kusuma; Astika, Ismiar; Farokah, Farokah; yunika, kanti; Marliyawati, Dwi (Diponegoro International Medical Journal, 2023)
ABSTRACK Background: COVID-19 can make smell and taste disorder due to Angitensin Converting Enzyme 2 (ACE2) binding to olfactory tractus and taste bud that affected by gender, age, comorbid and COVID-19 severerity.Aim: To analyze age, gender, comorbid and COVID-19 severity as risk factor for smell and or taste disorder in mild and moderate Covid -19 patient in SemarangMethods: Observational research used cross section design. Sample is COVID-19 patients age >10 years old with severity mild and moderate nonhospitalize that record on Health Center of Semarang City June – July 2021. Sampling metode using purposive sampling with secondary data. Association between variable analyze using Chi square or Fisher exact test, multivariate analyze with logistic regression.Results: Research on 4337 people, 2.0% smell disorder and 0.5% taste disorder. Prevalence COVID-19 mostly on women 50.5% and adult (20-60 years old) 82.5%. Risk factor gender, age and COVID-19 severity is not associated with smell and taste disorder on COVID-19 patients (p<0.05). Chronic liver disease as a risk factor only for smell disorder on COVID-19 patients (p 0.04, CI 3.029-786.993, RP 48.828). Conclusion: Chronic liver disease is a comorbid as a risk factor for smell disorder ini COVID-19 patients at Semarang. age, gender and other comorbid not as a risk factor for smell and or taste disorder.